2006
DOI: 10.1177/030089160609200407
|View full text |Cite
|
Sign up to set email alerts
|

Temozolomide and Radiotherapy as First-Line Treatment of High-Grade Gliomas

Abstract: We report the favorable results of a schedule combining radiotherapy and temozolomide in the treatment of patients with high-grade gliomas. The literature data and above all the findings of the phase III EORTC-NCIC 26981 trial suggest that actually the schedule can be used routinely in clinical practice. Further clinical studies, using temozolomide in combination with other agents, are required.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 31 publications
1
7
0
Order By: Relevance
“…Two of these studies, which reviewed 20 and 10 patients who received concurrent TMZ and radiation, respectively, found no benefit of the multimodality treatment when compared to RT alone in terms of OS. 17,18 In our study we have also found that there was no difference in the PFS and OS between the two groups of patients who received RT alone and combined TMZ-RT strategy. However, the limitation of our study was the retrospective nature of the review and the relatively small patient sample.…”
Section: Discussionsupporting
confidence: 60%
“…Two of these studies, which reviewed 20 and 10 patients who received concurrent TMZ and radiation, respectively, found no benefit of the multimodality treatment when compared to RT alone in terms of OS. 17,18 In our study we have also found that there was no difference in the PFS and OS between the two groups of patients who received RT alone and combined TMZ-RT strategy. However, the limitation of our study was the retrospective nature of the review and the relatively small patient sample.…”
Section: Discussionsupporting
confidence: 60%
“…Compared to the EORTC study, overall survival for both the RPA class 3 and 4 patients (17 months and 15 months) was in between the range observed for the EORTC radiotherapy only and combined arm (class 3: 15/21 months, class 4: 13/16 months) [18]. In another small, non randomized Italian study where TMZ was applied both neoadjuvant and adjuvant to RT compared to TMZ only at first relapse, time to progression was prolonged but survival was not different [9]. Thus, it seems that salvage therapy can, at least in part, compensate for the missing adjuvant chemotherapy and has an important impact on final outcome and should be carefully recorded in all trials for malignant glioma.…”
Section: Discussionmentioning
confidence: 63%
“…Median survival times of 18 months did not differ between the two arms. The same arms were used by Corsa et al, also from Italy, who investigated the use of RT and adjuvant TMZ in 64 patients with high grade gliomas [9]. In one of the two groups, simultaneous TMZ was added, but survival times did not improve.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is essential to verify the role of TMZ in the treatment of WHO grade III glioma. Since the above-mentioned landmark study of Stupp et al in 2005, there have been many phase II and III clinical studies of the treatment of HGG with TMZ in adults 4,9) . These trials have reported good outcomes, and our present results for patients with WHO grade III and IV gliomas are also favorable, with tolerable toxicity.…”
Section: Discussionmentioning
confidence: 99%